1999
DOI: 10.1073/pnas.96.12.6728
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via β1 integrins and mitogen-activated protein kinase determines human epidermal stem cell fate in vitro

Abstract: Human epidermal stem cells express higher levels of ␤1 integrins and are more adhesive than keratinocytes that are destined to differentiate. To investigate whether high ␤1 integrin expression and adhesiveness are essential for maintaining keratinocytes in the stem cell compartment, we introduced a dominant-negative ␤1 integrin mutant, CD8␤1, into cultured human keratinocytes, thereby interfering with ␤1 integrin function. Surface ␤1 integrin levels, adhesiveness, and mitogen-activated protein (MAP) kinase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
212
0
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(229 citation statements)
references
References 35 publications
11
212
0
6
Order By: Relevance
“…This DNp51B-dependent maintenance of integrin expression, which allows integrin-mediated emission of a growth promoting signal through the Erk pathway (Mainiero et al, 1997;Zhu et al, 1999), further supports a role of DNp51B in promoting the proliferation of keratinocytes. This regulation of integrin expression was not affected by p21 overexpression (unpublished result), suggesting that this regulation was not caused by p21 regulation mentioned above.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This DNp51B-dependent maintenance of integrin expression, which allows integrin-mediated emission of a growth promoting signal through the Erk pathway (Mainiero et al, 1997;Zhu et al, 1999), further supports a role of DNp51B in promoting the proliferation of keratinocytes. This regulation of integrin expression was not affected by p21 overexpression (unpublished result), suggesting that this regulation was not caused by p21 regulation mentioned above.…”
Section: Discussionsupporting
confidence: 52%
“…We further examined the effects of p51 and Notch1 expression on integrin-mediated signaling, particularly on extra-cellular signal-regulated kinase (Erk) pathway, which is known to function down-stream of integrin signaling (Mainiero et al, 1997;Zhu et al, 1999). Indeed, exogenous expression of DNp51B induced phosphorylation of Erk and Mek1/2 (Figure 5f), and the reduction of DNp51B by siRNA method decreased phosphorylation (Figure 5d), together suggesting that DNp51B-dependent expression of the integrins leads to the activation of Mek1/2-Erk pathway.…”
Section: Dnp51b Induces Integrin Expression In Keratinocytesmentioning
confidence: 99%
“…This is consistent with the initial transient release of [ 3 H]AA experienced by cells on the FN substrate being due to the ligation and clustering of integrin receptors, because it has been previously shown that clustering FN receptors stimulates AA release (Auer and Jacobson, 1995;Szabo et al, 1995;Haimovich et al, 1999;Zhu et al, 1999;Whitfield and Jacobson, 1999). Additional assays were conducted to test this possibility ( Figure 6A).…”
Section: Arachidonic Acid Releasesupporting
confidence: 56%
“…For example, integrins are key regulators of the coordinated differentiation of many epithelial tissues. The functions of the ␤1 subfamily of integrins are particularly well understood in mammary development (Faraldo et al, 1998;Bissell et al, 1999) and in the differentiation of the epidermis (Watt, 1998;Zhu et al, 1999). However, integrins clearly play a role in other epithelia as well.…”
mentioning
confidence: 99%